JOB SATISFACTION AMONG DOCTORS WORKING AT TEACHING HOSPITAL OF BAHAWALPUR, PAKISTAN - Ghazali, Syed Shakir Ali; Shah, Ijaz Ahmad; Zaidi, Syed Arif Ahmed; Tahir, M. H. (Journal of Ayub Medical College Abbottabad, 2007)
Background: Doctor’s profession has long been among one of the most attractive professions in Pakistani society, but doctors are increasingly getting dissatisfied with their jobs. The focus of this study is to point out the most prominent factors of job dissatisfaction among doctors working at Bahawal-Victoria Hospital / Quaid-e-Azam Medical College, Bahawalpur. Methods: A questionnaire was mailed to a random sample of 60 out of 244 doctors working at BahawalVictoria Hospital / Quaid-e-Azam Medical College, Bahawalpur. Questions included satisfaction with respect to designation, income, service structure, career prospects etc. Results: Overall 56% doctors were not satisfied with the level of their income. It is found that 92% of all the doctors were neither satisfied with the present service structure nor with the career prospects in Pakistan. Further, 78% of the doctors would like to serve abroad. Main factors contributing towards job satisfaction were designation and working environment whereas service structure turned out to be the source of dissatisfaction. Conclusions: Most of the doctors in all ranks and with different qualifications were not found satisfied with their job due to lack of proper service structure and low salaries. Keywords: Career prospects; cross-sectional study; job satisfaction; medical care; service structure